Study guides

☆☆

Q: What is 9x-3(x plus 13y)?

Write your answer...

Submit

Still have questions?

Related questions

(y2+13y+22)/(y+2) = (y+11)

-2x+13y=11 13y=2x+11 y=2x/13 + 11/13

If y2 + 13y = 40, then y ~ 15.55If y2 + 13y = 0, then y = -13Improved Answer:-y2+13y+40 = 0(y+5)(y+8) = 0Therefore: y = -5 and y = -8

It can be simplified to: 12x-3w+13y

13y+3z+8

If you mean: 4y^2 +3 -13y then the expression is (4y-1)(y-3) when factored

42+4y -12 = 13y -12 -2y 4y -13y+2y = 12 -12 -42 -7y = -42 y = 6

(x - 13y)(x + 13y)

Do you mean: y2+13y+40 = 0 If so then when factored: (y+5)(y+8) = 0 Therefore: y = -5 and y = -8.

4y + 3w + 4x + 9y + 7x - 7w (combine like terms)-4w + 11x + 13y

-26x

3x - 8y + 2x - 5 - 5y = 5x -13y - 5

This simplifies to 6+13y If you meant 9+7y-(3+6y) then it becomes 6+y It is not clear from the problem which you meant.

a) 4x+13y=40 b) 4x+3y=-40c) multiply b per(-1)=-4x-3y-40d) sum a and c: 4x+13y-4x-3y=40-(-40)=>10y=80 => y=8to find x replace y per its value in a or b and get x=-16

It is a quadratic expression which when factored is (2y+3)(y+5)

y= -3/13​​

Without an equality sign and not knowing the plus or minus values of some of the given terms it can't be considered to be an equation.

x2 + 8xy + 15y2 = (x + 3y) (x + 5y)

(2y + 5)(y - 9)

(y - 1)(4y - 9)

It is like saying, "How much is 8 yams plus 2 yams plus 3 yams?" Add the numbers: 8+2+3 = 13. The answer is the number of yams. 8y+2y+3y = (8+2+3)y = 13y.

Yes, if its for a kid you can make it under 13y/o so they can only say certain things, 13y/o and up you can type whatever but only to other 13y/o and still some words are banned.. Some people make inappropriate clothing.. Only a few. I have only seen 1.

5y - 4 + 9y - 1y + 15= 5y + 9y - 1y + 15 - 4= (5 + 9 - 1)y + (15 - 4)= 13y + 9

Yes she has a 13y year old boyfriend

13y-6